Forensic Soil Investigation from the 16S rDNA Profiles of Soil Bacteria Obtained by Denaturing Gradient Gel Electrophoresis - Anothai Sanachai (Science Faculty of Chiang Mai University, 2019)
The forensic investigation of soil evidence had been examined in this study. Soil evidence from shoes (KKU11) was compared with soil samples from mock crime scenes (KKU1, KKU2, KKU3, KKU4, KKU5), the site around the mock crime scenes (KKU6, KKU7) and non-relevant areas (NM, BP, TP). The bacterial quantities were examined by pour plate technique. The physical and chemical characteristics of soil samples were also investigated. Results showed that bacterial quantities and soil characteristics gave no clue for soil sample origin because their results were not significantly different. Thus, the comparison of bacterial DNA was then performed. Bacterial DNA was extracted from soil samples and the 16S rDNA was subsequently amplified. The PCR product was analyzed by denaturing gel electrophoresis. A total of approximately 101 DNA bands were displayed. The 16S rDNA profiles were compared and clustered by UPGMA method. The similarity indexes of soil samples ranged 0.48-1.00. Three groups of soil samples were constructed. The accuracy of dendrogram was then evaluated by cophenetic correlation (r) value. The value of 0.89 was demonstrated indicating that the correlation coefficient and similarity coefficient values are well corresponded. Hence, the dendrogram is considerably accurate. Interestingly, all samples taken from mock crime scenes were in the same group. In addition, KKU11 had the most similarity to KKU1. These results elucidated that the origin of soil could be identified by similarity comparison of soil bacterial 16S rDNA profiles separated by the DGGE method.